1994
DOI: 10.1046/j.1523-1739.1994.08010039.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Conservation of Wild Plant Species: Time to Reassess the Genetic Assumptions and Implications of Seed Banks

Abstract: Ex situ conservation of wiM plant species through motosy, Pases 39--49 Volume&No. l, March 1994ciones sobre la relaci6n y signiflcaci6n evolutiva de la va~acion gen&tica de alelos y cuantitativa en poblaciones silvestre~ Se necesitan datos iniciales y continuos sobre la suerte de diferentes tipos de varlaci6n gendticas para deterrainar el #xito relativo o el fracaso de los mdtodos de con-servaci6n ex situ y para testear los supuestos de los programas corriente~ La conservaci6n in situ de ecosistemaspuede ofrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 23 publications
1
49
0
4
Order By: Relevance
“…Hartl and Clark (1989) suggested that the average time a neutral allele will persist in a population is a function of population size and the allele's initial frequency. Given that seed banks are temporary storehouses of genetic variation, the rate of loss or change in allele frequency under the effects of storage and removal is likely to be higher than for natural populations, particularly since the collection is only a sample of the variation within the source population (Hamilton 1994). Though a concern, the phenomenon may not be as significant as the effects of poor sampling in the field and poor regeneration practices.…”
Section: Ex Situ Conservation Of Orchidsmentioning
confidence: 99%
“…Hartl and Clark (1989) suggested that the average time a neutral allele will persist in a population is a function of population size and the allele's initial frequency. Given that seed banks are temporary storehouses of genetic variation, the rate of loss or change in allele frequency under the effects of storage and removal is likely to be higher than for natural populations, particularly since the collection is only a sample of the variation within the source population (Hamilton 1994). Though a concern, the phenomenon may not be as significant as the effects of poor sampling in the field and poor regeneration practices.…”
Section: Ex Situ Conservation Of Orchidsmentioning
confidence: 99%
“…Taking this into consideration, it appears that a more feasible approach for protecting P. mira Koehne germ plasm would be ex situ conversation based on seed banks. [32] Thus, for the purpose of ex situ conversation, samples of high quality should be collected from different populations. Although this study and our previous ones [17,29] covered a considerable area, the number of P. mira Koehne accessions collected is still limited.…”
Section: Conservation Recommendations For Prunus Mira Koehnementioning
confidence: 99%
“…Las accesiones recolectadas son caracterizadas, catalogadas y registradas en una base de datos para el control de la trazabilidad del germoplasma, desde que entran en la colección hasta que salen en forma de planta para los trabajos de restitución en campo, metodología basada en lo indicado por Bacchetta et al (2008) y fundamentada en determinados trabajos básicos (Falk, 1987;Cohen et al, 1991;Hamilton, 1994;Iriondo, 2001;Linington & Pritchard, 2001; IPGRI/FAO/FLD, 2004), y que en concreto para la flora valenciana ya fuera expuesta por Ferrer-Gallego et al (2013a).…”
Section: Materials Y Métodosunclassified